Testicular biometry of Nellore (Bos taurus indicus) and crossbred bulls (Bos taurus indicus x Bos taurus taurus) at 20 and 24 months of age - Valentim, Renato; Arruda, Rubens Paes; Barnabe, Renato Campanarut; Alencar, Maurício Mello (Brazilian Journal of Veterinary Research and Animal Science, 2002)
The objective of the present study was to evaluate the effects of age and genetic group in bulls, and determine the relationship between these two factors on testicular biometry (scrotal circunference and testicular consistency). One hundred and ninety Nellore Bulls and 447 crossed Nellore-European bulls were used when aged 20 and 24 months. Scrotal circunference and testicular consistency were found to be influenced by genetic group, age and genetic group and age interaction. Higher scrotal circunference and testicular consistency were fond in crossed bulls as compared to Nellore ones, both at 20 and 24 months of age.